IDENTIFIKASI JAMUR ENDOFIT DARI TANAMAN KARET DAN UJI In-vitro ANTI MIKROBA TERHADAP Rigidoporus microporus - Dawolo, Baziduhu; Puspita, Fifi; Armaini, Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
White root fungus (Rigidoporus microporus) is a major pathogen in the rubber plant that is difficult to control because it has a structure that survives in plant tissue.  Biological control of endophytic fungi is very potential to control  Mushrooms JAP.  This research was conducted at Plant Disease Laboratory of Agriculture Faculty of Riau University and Photomikografi Laboratory, FMIPA Organic Chemistry Laboratory Department of Biology, University of Riau, Simpang Baru Campus Tampan District, Pekanbaru.  Starting from March to June 2017 with the aim of Identification of morphological cultivation of endophytic fungi and In-Vitro microbial test on Rigidoporus microporus in rubber plant.  The study consisted of site survey, sampling, tool sterilization, PDA & PDB media manufacture, fungi isolation, rubber plant tissue incubation, purification and observation. Based on the results of isolation and identification of endophytic fungi from plant tissue obtained 3 isolates where there are 2 types of Aspergilus SP fungus and 1 type of Trichoderma sp.  All three isolates are potential endophytic fungi to control JAP disease in rubber. Hypovirulensi test results did not produce symptoms of chlorosis or necrosis after inoculated Trichoderma 48 hours after incubation. Observation of secondary metabolite Trichoderma sp endophytes after 14 days incubated in a petridish showed metabolite results with a mean of 0.75 cm clear zone. Keywords: Rigidoporus microporus, Identification, Endophytic Fungi